THE QUALITY OF BOAR FROZEN SEMEN DILUTED IN BTS® AND MII® WITH DIFFERENT CRYOPROTECTANT SUPPLEMENTED WITH SODIUM DODECYL SULPHATE - Nancy Diana Frederika Katerina Foeh; Raden Iis Arifiantini; Tuty Laswardi Yusuf (Jurnal Kedokteran Hewan, 2017)
This research was aimed to study the effect of administration of glycerol and dimetilacetamida (DMA) in BTS® and MIII®extender supplemented with sodium dodecyl sulphate (SDS) on boar frozen semen. A number of four boars were used in this study for semen collection (n=20). The collected semen was evaluated both macroscopically and microscopically. In this study, only the semen that demonstrated70% sperm motility, 200.106/mL sperm concentration, and20% sperm abnormalities were used and divided into eight tubes. A number of 4 tubes were diluted with 5 mL of BTS, and the rest with 5 mL MIII. The sampel was stored at 20-22° C for 2 hours, followed by centrifugation for 15 minutes (at 2000 rpm), and taken of pellet with 1 ml supernatant. The pellet that was resulted from centrifugation using BTS, then re-diluted with BTS-glycerol 5% (BTSG), BTS DMA 5% (BTSD), BTS-glycerol 5% and SDS (BTSG-S), BTS-DMA 5% and SDS (BTSD-S). Four other pellets that were centrifuged with MIII also re-diluted with MIII-glycerol 5% (MIIIG), MIII-DMA 5% (MIIID), MIII-glycerol 5% and SDS (MIIIG-S), MIII-DMA 5% and SDS (MIIID-S). Next, all of diluted semen were inserted into 0.5 mL straw and equilibrated for 2 hours (4° C), then frozen and stored in liquid nitrogen. The evaluation of frozen semen quality was conducted at 24 hours after frozen. The result of this study showed that post-thawing motility of spermatozoa in BTSD-S (40.17±0.2%) was found higher (P0.05) compared to seven other dilution processes. Therefore, it is concluded that the concentration of 5% DMA that supplemented with SDS in BTS dilution much better for maintaining boars frozen semen quality.